2021
DOI: 10.3390/nano11020557
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selenium Nanoparticles on the Osteogenic Differentiation of MC3T3-E1 Cells

Abstract: Reactive oxygen species (ROS) regulate various functions of cells, including cell death, viability, and differentiation, and nanoparticles influence ROS depending on their size and shape. Selenium is known to regulate various physiological functions, such as cell differentiations and anti-inflammatory functions, and plays an important role in the regulation of ROS as an antioxidant. This study aims to investigate the effect of selenium nanoparticles (SeNPs) on the differentiation of osteogenic MC3T3-E1 cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 69 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…SeNPs and SeNWs were selectively synthesized by reducing aqueous solutions of sodium selenite with ascorbic acid and glucose respectively, as previously reported [45,46]. In a typical procedure of synthesizing SeNPs, 100 mM of sodium selenite aqueous solution was mixed with 100 mM of ascorbic acid, and the solution pH was adjusted to 7.1 using NaOH or HCl.…”
Section: Synthesis Of Senps and Nanowiresmentioning
confidence: 99%
“…SeNPs and SeNWs were selectively synthesized by reducing aqueous solutions of sodium selenite with ascorbic acid and glucose respectively, as previously reported [45,46]. In a typical procedure of synthesizing SeNPs, 100 mM of sodium selenite aqueous solution was mixed with 100 mM of ascorbic acid, and the solution pH was adjusted to 7.1 using NaOH or HCl.…”
Section: Synthesis Of Senps and Nanowiresmentioning
confidence: 99%
“…SeNPs were synthesized by the reduction method, as previously reported by our group [ 26 ]. Briefly, an aqueous solution of sodium selenite (100 mM) was mixed with an aqueous solution of ascorbic acid (100 mM) using magnetic stirring, and the pH was maintained at 7.1 using NaOH (0.1 M) or HCl (0.1 M).…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the oxidase-like activity of SeNPs, as previously reported by our group [ 26 ]. Briefly, the catalytic activity (i.e., oxidation of the peroxidase substrate) of SeNPs was observed in 3,3′,5,5′-tetramethylbenzidine (TMB) in the presence of hydrogen peroxide (H 2 O 2, Sigma–Aldrich, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Bi 2 Se 3 has favorable biocompatibility, greatly facilitating their promising application. Bi 2 Se 3 was reported to be degraded, and Se released from Bi 2 Se 3 played an important role through selenoproteins to protect membranes and tissues [ 16 ], prevent cancers [ 17 , 18 ] and regulate immunity [ 19 ]. It was reported that Bi 2 Se 3 nanoplates were intraperitoneally injected into mice at a high dose of 20 mg/kg and finally, 93% nanoplates were metabolized with few side-effects within the 90-day long-term period [ 20 ].…”
Section: Introductionmentioning
confidence: 99%